Skrining Fitokimia Kelopak Bunga Rosella (Hibiscus sabdariffa L.) dalam Bentuk Bunga Kering dan Bubuk Halus - Hafiza Tara Devi; Minda Azhar (Lembaga Yasin AlSys, 2025)
Medicinal plants are vital sources of natural bioactive compounds with potential applications in pharmaceuticals, cosmetics, and functional foods. One such plant with high potential is Roselle (Hibiscus sabdariffa L.), known to contain various secondary metabolites such as flavonoids, alkaloids, saponins, and terpenoids. This study aims to compare the phytochemical profiles of Roselle calyces in two different physical forms—whole dried flowers and powdered form—and to assess the effect of physical treatment on the presence of secondary metabolites. The samples were dried, ground, and sieved to obtain a fine powder, followed by qualitative phytochemical screening using specific reagents: Culvenor-Fitzgerald for alkaloids, Shinoda and cyanidin tests for flavonoids, foam test for saponins, 1% FeCl₃ for tannins, and Liebermann–Burchard test for terpenoids and steroids. The results showed that both sample forms tested positive for alkaloids, flavonoids, saponins, and terpenoids, while tannins and steroids were not detected. These consistent findings suggest that proper drying and grinding processes do not significantly degrade the main active compounds in Roselle. The study concludes that the physical form of Roselle calyces (whole or powdered) does not qualitatively affect its phytochemical profile. These results provide a foundation for optimizing the use of Roselle’s secondary metabolites in phytopharmaceuticals or plant-based product applications.